Dynamic changes in myeloid-derived suppressor cells during the menstrual cycle: A pilot study - Xu, Qiying; Liu, Huifang; Qile, Muge; Wuren, Tana (Frontiers in Medicine, 2022)
Various studies have described the roles of myeloid-derived suppressor cells (MDSCs) in pathological conditions, but relatively few have described them under normal physiological conditions. Accumulation of MDSCs is important creating an anti-inflammation environment, which is essential for fertilized egg implantation. This study was designed to record the dynamic changes in MDSCs composition during the menstrual period (MP) and ovulation period (OP) in healthy volunteers over the course of a single menstrual cycle to explore the association between MDSCs and the menstrual cycle under normal physiological conditions. The ratio of MDSCs was higher in MP samples, whereas the activity of Arg-1 was higher during the OP window. There was a negative correlation between the ratio of MDSCs and the percentage of lymphocytes and a positive correlation between MDSCs and prostaglandin E2 (PGE2). Furthermore, regular changes in the ratio and function of MDSCs in the peripheral blood were observed during menstruation, all of which corresponded to the cycle stage. During menstruation, MDSCs may promote endometrial repair, whereas they promote pregnancy during the OP.These findings may help to better understand the pathophysiology of pregnancy-related complications and lay a foundation for improving perinatal outcomes.